Factors of the Competitiveness of Enterprise - Marčinskas, Albinas; Diskienė, Danutė (Ekonomika, 2001)
The article deals with the role of different factors (external and internal) in the development of the competitiveness of enterprises. The main emphasize is put on the managerial factor as the success in competition more and more depends not on the production function but on the quality and effectiveness of management. That is why it is essential to be aware of the situation of the managerial functions at enterprises. Results of the research in different industrial enterprises allowed to evaluate the orientations of the performing of main managerial functions - planning, organizing, leadership and control. It became clear that the managerial behaviour of our managers is still strongly affected by the past experience which is in conflict with nowadays transformation realities. So striving to develop the ability to compete in the Western economic system, it is important to change managerial attitudes by applying the new management philosophy.